Pengaruh Rasio Solvabilitas, Rasio Aktivitas Dan Rasio Profitabilitas Terhadap Harga Saham Industri Minyak Dan Gas Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Arif Alianto (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of solvency ratio, activity ratio, and profitability ratio on the stock prices of oil and gas industry companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research method used is quantitative with a purposive sampling technique, involving 20 companies as samples over five years. The independent variables used are Debt to Asset Ratio (DAR) to measure solvency, Total Asset Turnover (TATO) to measure activity, and Return on Asset (ROA) to measure profitability, while the dependent variable is stock price. The results show that the activity ratio (TATO) has a significant effect on stock prices, whereas the solvency ratio (DAR) and profitability ratio (ROA) do not have a significant partial effect. However, simultaneously, these three ratios have a significant effect on stock prices. This study provides insights for investors in assessing the financial performance of companies and serves as a reference for companies to enhance their investment attractiveness.